Gamma Transcranial Alternating Current Stimulation Enhances Working Memory Ability in Healthy People: An EEG Microstate Study - Binbin Gao; Jinyan Zhang; Jianxu Zhang; Guangying Pei; Tiantian Liu; Li Wang; Shintaro Funahashi; Jinglong Wu; Zhilin Zhang; Jian Zhang (Brain Sciences)
Background:Working memory (WM) is a core cognitive function closely linked to various cognitive processes including language, decision making, and reasoning. Transcranial alternating current stimulation (tACS), a non-invasive brain stimulation technique, has been shown to modulate cognitive abilities and treat psychiatric disorders. Although gamma tACS (<semantics>γ</semantics>-tACS) has demonstrated positive effects on WM, its underlying neural mechanisms remain unclear. Methods: In this study, we employed electroencephalogram (EEG) microstate analysis to investigate the spatiotemporal dynamics of <semantics>γ</semantics>-tACS effects on WM performance. Healthy participants (N = 104) participated in two-back and three-back WM tasks before and after two types (sine and triangular) of <semantics>γ</semantics>-tACS, with sham stimulation as a control. Results: Our results revealed that <semantics>γ</semantics>-tACS improved performance in both the two-back and three-back tasks, with triangular <semantics>γ</semantics>-tACS showing greater accuracy improvement in the three-back task than the sham group. Furthermore, <semantics>γ</semantics>-tACS significantly modulated EEG microstate dynamics, specifically downregulating microstate Class C and upregulating microstate Classes D and B. These changes were positively correlated with reduced reaction times in the three-back task. Conclusions: Our findings establish microstate analysis as an effective approach for evaluating <semantics>γ</semantics>-tACS-induced changes in global brain activity and advance the understanding of how <semantics>γ</semantics>-tACS influences WM.